Sensory Perception in Lumbosacral Radiculopathy with Radicular Pain: Feasibility Study of Multimodal Bedside-Suitable Somatosensory Testing - Vaitkus, Alfredas; Šipylaitė, Jūratė (Acta medica Lituanica, 2021)
Background. Somatosensory testing could be useful in stratifying pain patients and improving pain treatment guidelines. Bedside-suitable techniques are searched for application in daily clinical practice. This study aimed to characterize chronic unilateral lumbosacral radiculopathy (LSR) patients with radicular pain using multimodal bedside-suitable somatosensory testing.Materials and methods. We evaluated 50 chronic unilateral LSR patients with radicular pain (LSR group) and 24 controls (Control group). Sensory testing was performed using a battery of bedside sensory tests (10g monofilament, 200–400 mN brush, Lindblom rollers with controlled 25°C and 40°C temperature, and 40g neurological pin and investigator’s finger pressure). Participants had to rate their sensory perceptions on both legs at multiple test points within L3 to S2 dermatomes. Characteristics of the testing process and sensory disturbances were analyzed.Results. LSR group showed sensory disturbances in 82% of patients. The Control group showed no sensory disturbances. Sensory testing took longer (p < 0.001) in the LSR group (29.3 ± 6.5 minutes per patient) than in the Control group (20.5 ± 5.2). Nine sensory phenotypes were detected in the LSR group according to individual sensory disturbances within 5 superficial tests.Conclusions. The applied multimodal bedside-suitable somatosensory testing battery is suitable for sensory evaluation and characterization of LSR patients. Grouping of allied sensory phenotypes revealed some tendencies in pain intensity characteristics.
Keywords: sensory testing; bedside testing; sensory phenotyping; back pain; lumbosacral radiculopathy